Associations of emotional arousal, dissociation and symptom severity with operant conditioning in borderline personality disorder - Paret, Christian; Schmahl, Christian (Psychiatry research, 2016)
Those with borderline personality disorder (BPD) display altered evaluations regarding reward and punishment compared to others. The processing of rewards is basal for operant conditioning. However, studies addressing operant conditioning in BPD patients are rare. In the current study, an operant conditioning task combining learning acquisition and reversal was used. BPD patients and matched healthy controls (HCs) were exposed to aversive and neutral stimuli to assess the influence of emotion on learning. Picture content, dissociation, aversive tension and symptom severity were rated. Error rates were measured. Results showed no group interactions between aversive versus neutral scenes. The higher emotional arousal, dissociation and tension, the worse the acquisition, but not reversal, scores were for BPD patients. Scores from the Borderline Symptom List were associated with more errors in the reversal, but not the acquisition phase. The results are preliminary evidence for impaired acquisition learning due to increased emotional arousal, dissociation and tension in BPD patients. A failure to process punishment in the reversal phase was associated with symptom severity and may be related to neuropsychological dysfunctioning involving the ventromedial prefrontal cortex. Conclusions are limited due to the correlational study design and the small sample size.
Gesehen am 16.07.2019
Available online 26 July 2016